Trzy estetyki adresowania - Tiupa, Walerij (Er(r)go. Teoria - Literatura - Kultura, 2015)
Valery Tyupa Russian State University for the Humanities "Three Aesthetics of Addressing" Examining 20th century art, the author looks at avangarde art movements which in their departure from classical models of artistic expression shifted their focus from the object to the reciever in order to influence his or her spiritual experience. The transition from creativity to receptivity in the process of artistic creation is represented as typical of non-classical aesthetics which favours work’s openness and fragmentariness and thus activates the “third partcipant in the game”—the reader/the receiver. Referring to Russian avantgarde artists, the author explores the rise of the significance of “the third” and places it in the context of political power and the rules of the market.